Comparative evaluation of five different storage media and temperature effect on human periodontal ligament fibroblast viability - Zahra Sadat Madani; Zinat Sadat Rezaie; Ebrahim Zabihi; Zeinab Abedian (Babol University of Medical Sciences, 2019)
Introduction: Following dental avulsion, the immediate recommended treatment is tooth replantation to avoid adverse effects. Therefore, the tooth must be stored in a physiological storage medium to preserve the viability of the periodontal ligament fibroblast (PDLF) cells during transportation to dental office. The aim of this study was to determine the effect of several storage media in preserving the viability of human PDLF cells at different times and temperatures. Material & Methods: In this experimental study, the human PDL cells were obtained from the healthy extracted third molars and cultured in Dulbecco's Modified Eagle Medium (DMEM). The studied media were DMEM (10% FBS + 1% penicillin G Na (10000 IU) + 1% streptomycin (10 mg)), tap water, sterilized whole milk, zero fat milk and soy milk. After the cells had reached sufficient density in the plate, they were added to the experimental media and kept at 1, 2, 4 and 24 hours at 4° and 37oCentigrade. After incubation, the cell viability was determined by tetrazolium salt-based colorimetric (MTT) assay. The results were statistically analyzed  using Kruskal-Wallis and post hoc Tests. Results: Whole milk and DMEM showed significantly higher protective effect than other media. The viability of PDL cells had significant difference at 4oC compared to 37oC at 4 and 24 h in DMEM group and at 24 h in whole milk group (p≤0.05). Conclusion: The results have suggested that the whole milk like DMEM have enough essential nutrients for PDLFs and have confirmed the hypothesis that the milk similar to HBSS or DMEM might be effective in preserving the PDLF cells.